Pembinaan Pemuda dan Pengelolaan Sampah: Program Kerja Utama KKN Tematik UCY di Kampung Giwangan - Sarumaha, Yenny Anggreini; Setiawan, Aldi; Sylvianie, Lulu (CV. Kurnia Grup, 2025)
UCY Thematics Community Service Program (KKN) is a program packaged as community service, representing a synergy between campus learning and community life. UCY, as a national campus concerned with the progress of the Indonesian nation and state, has a responsibility to contribute to village development thru KKN activities. In the implementation of this community service, there are several falgship programs, including youth and sports development in collaboration with Kampung Giwangan and waste management in the community. The morning youth and sports development program by KKN students in Kampung Giwangan was considered successful because it increased youth participation, strengthened social interaction, and had a positive impact on the health and togetherness of the community, despite some challenges. The socialization activities on plastic waste management in Kampung Giwangan, which focused on teenagers and parents, were categorized as yielding positive results because they increased awareness of environmental cleanliness. Thru interactive methods and active participation from the participants, waste management becomes an activity that can be continued even after the KKN program is over. Nevertheless, the continuation of this program requires a more sustainable strategy. Thru this activity, students learn to hone their soft skills to build partnerships, cross-disciplinary or cross-competency teamwork, and leadership in managing the potential of the village in the KKN area.